The financialization of safety: The impact of stock buybacks on public safety and emergency management resources - Erik Xavier Wood (Journal of Emergency Management, 2026)
This study examines how corporate stock buybacks in the United States compromise public safety, focusing on three critical industries: aviation, utilities, and rail transport. By prioritizing shareholder returns through repurchases, companies may underfund employee training, equipment maintenance, and operational safety. Through a focused review of the available literature and an analysis of three case studies—a major airline manufacturer, a large railroad operator, and a leading electric and gas utility—this research examines how financialized corporate priorities plausibly contributed to safety lapses, resulting in preventable disasters, loss of life, and added strain on emergency management systems. The analysis yields four actionable recommendations that call for policy reform and ethical oversight to better balance shareholder interest with long-term accountability and public welfare. It also identifies a notable gap in academic literature on this issue, underscoring the need for further research. The findings are relevant to scholars, policymakers, and practitioners concerned with safety, regulation, and the unintended consequences of corporate financial strategies.